Investigation of parasitic contamination of protein products produced in Isfahan industrial slaughterhouse (Revista de Investigaciones Universidad del Quindío, 2023)
This study aims to investigate the common and important parasitic infections that reduce the nutritional value and also cause serious damage and disrupt the functioning of systems such as the liver and bile ducts as a vital organ of the human body and livestock. In order to investigate the mentioned parasitic infections in the autumn season, 60,881 livestock, including 32,213 sheep, 21,368 goats, 6,186 cows, 1,059 ostriches and 55 camels were slaughtered in Fasaran Slaughterhouse in 2022. Method: According to the working timetable and the existence of two slaughter lines, organs such as liver, lung, heart and carcass are examined macroscopically, then samples suspected of contamination are separated for microscopic examination. Results: The prevalence rate of hydatid cyst parasite was 49.44%, including 30.02% in sheep, 6.78% in goats, and 12.63% in cows. Moreover, the severity of infection in the liver of sheep, goats, and cows was 10, 1.04, and 2.89%, respectively. Also, the severity of lung contamination in sheep, goats, and cows was 20.02, 5.73 and 9.46% respectively. The prevalence rate of cysticercosis parasite was 0.38%, in a way that, infection rate in the carcasses of sheep, goats, and cows was 0.27%, 0.60%, and 0.40%, respectively. Conclusion: According to the results, it can be concluded that parasitic infection can play an important role in reducing the nutrients of infected tissues, and in case of human infection, pathological complications can affect the functioning of body organs and disrupt and cause serious harm to human health.
Keywords: liver histopathology; cysticercosis; fasciola; dicrocoelium; hydatid cyst